2011
DOI: 10.1111/j.1742-4658.2011.08356.x
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal targeting of cytochrome P450s to endoplasmic reticulum and mitochondria: the concept of chimeric signals

Abstract: Summary Targeting signals are critical for proteins to find their specific cellular destination. Signals for protein targeting to the endoplasmic reticulum (ER), mitochondria, peroxisome and nucleus are distinct and the mechanisms of protein translocation across these membrane compartments also vary markedly. Recently, however, a number of proteins have been shown to be present in multiple cellular sites such as mitochondria and ER, cytosol and mitochondria, plasma membrane and mitochondria, and peroxisome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 87 publications
7
75
0
Order By: Relevance
“…Although cross-contamination may have occurred between subcellular fractions during sample processing, distinct patterns of expression were seen in the two fractions arguing against the hypothesis that apparent P450 expression in mitochondrial and soluble fractions was due to contamination with microsomes. Importantly, it is now recognized that many "microsomal" P450s are also expressed in mitochondria, cytosol, and plasma membrane (Neve and Ingelman-Sundberg, 2008;Avadhani et al, 2011). Import into the mitochondrion involves an initial transit through the cytosol, which may explain the cytosolic localization of CYP3A4 in the present study, given the clear signal observed in the mitochondrial fraction.…”
Section: Discussionsupporting
confidence: 59%
“…Although cross-contamination may have occurred between subcellular fractions during sample processing, distinct patterns of expression were seen in the two fractions arguing against the hypothesis that apparent P450 expression in mitochondrial and soluble fractions was due to contamination with microsomes. Importantly, it is now recognized that many "microsomal" P450s are also expressed in mitochondria, cytosol, and plasma membrane (Neve and Ingelman-Sundberg, 2008;Avadhani et al, 2011). Import into the mitochondrion involves an initial transit through the cytosol, which may explain the cytosolic localization of CYP3A4 in the present study, given the clear signal observed in the mitochondrial fraction.…”
Section: Discussionsupporting
confidence: 59%
“…endoplasmic reticulum and mitochondrial targeting, including CYP1A [79,80] and CYP2E1 [79,81]. Vertebrate CYP11A and CYP11B/11C are ohonologues that duplicated during 2R (table 1).…”
Section: (I) Mitochondrial Clan Cypsmentioning
confidence: 99%
“…Importantly, CYPs are mainly located in the ER membranes, although some CYPs could be also found in mitochondria (Avadhani et al. 2011; Knockaert et al. 2011).…”
Section: Introductionmentioning
confidence: 99%